There’s nothing to beat a backward clock: A rejoinder to Adams, Barker and Clarke - WILLIAMS, John N. (Institutional Knowledge at Singapore Management University, 2016)
Neil Sinhababu and I presented Backward Clock, anoriginal counterexample to Robert Nozick’s truth-tracking analysis ofpropositional knowledge. Fred Adams, John Barker and Murray Clarke argue that Backward Clock is no such counterexample. Theirargument fails to nullify Backward Clock whichalso shows that other tracking analyses, such as Dretske’s and one that Adams et al may well have in mind, are inadequate.